1998
DOI: 10.1046/j.1365-3083.1998.00336.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Adhesion Molecule Expression on Porcine Mononuclear Cell Populations

Abstract: Adhesion molecule expression was analysed on porcine blood and lymphoid organ CD4+ CD8 naive T helper (Th) lymphocytes, CD4+CD8+ memory Th lymphocytes (particular to the pig), CD4-CD8high cytotoxic T (Tc) lymphocytes, CD4 CD8low NK cells (CD3- in the pig), CD4-CD8- T-cell receptor-gammadelta-positive (TCRgammadelta+) lymphocytes, B lymphocytes and monocytes. While CD44 expression was relatively homogeneous amongst mononuclear cells, differences were noted for the integrins. Blood naive Th lymphocytes were CD49… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…‘Leucocyte‐functioning antigen‐1’ (LFA‐1) is an adhesion molecule expressed virtually on all leucocytes. It is a heterodimeric integrin that consists of two subunits, the α‐ and β2‐chains, characterized by the cluster of differentiation (CD) nomenclature CD11a/CD18 [1, 2]. LFA‐1 is pivotal in inflammation and bound to its ligand, intercellular adhesion molecule 1 (ICAM‐1), LFA‐1 is responsible for the homing of T cells to peripheral lymph tissue [3], and for leucocytes transmigration into inflamed tissue via firm adhesion [4–6].…”
Section: Introductionmentioning
confidence: 99%
“…‘Leucocyte‐functioning antigen‐1’ (LFA‐1) is an adhesion molecule expressed virtually on all leucocytes. It is a heterodimeric integrin that consists of two subunits, the α‐ and β2‐chains, characterized by the cluster of differentiation (CD) nomenclature CD11a/CD18 [1, 2]. LFA‐1 is pivotal in inflammation and bound to its ligand, intercellular adhesion molecule 1 (ICAM‐1), LFA‐1 is responsible for the homing of T cells to peripheral lymph tissue [3], and for leucocytes transmigration into inflamed tissue via firm adhesion [4–6].…”
Section: Introductionmentioning
confidence: 99%
“…The results had not yet demonstrated that T cells were activated. Consequently, analyses turned to the responding T-cell subpopulations, identified by their upregulation of CD25 (1,3). PBMC obtained at 6 days postvaccination were stimulated in vitro with VP4-0 or the T-cell-B-cell tandem.…”
mentioning
confidence: 99%
“…We determined the challenge virus-specific adaptive memory T cell responses in the lung draining TBLN and blood. Activated T-helper/memory cells and NK cells exhibit enhanced surface expression of β1 integrins such as CD49d in pigs [28], and hence, we used CD49d as a surrogate marker for antigen-experienced cells in flow cytometry analysis. Both the Nano11-SwIAV and NanoS100-SwIAV vaccines augmented the frequencies of challenge virus-specific T cell responses in pigs (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The memory T cells responses in TBLN were characterized by multi-color flow cytometry (Figure 4A-I), and the standard gating strategy was followed to detect CD49d + IL-17A + and IFNγ + T-helper/memory cells and cytotoxic T lymphocytes (CTLs) (Supplementary Figure S1B,C). The expression of the CD49d integrin was increased upon activation of T cells and can be used as a surrogate marker for antigen-experienced or memory T cells [28]. The frequencies of total T-helper/memory cells were significantly downregulated (p < 0.0001) in all of the SwIAV H1N1-OH7-challenged pigs compared to the mock animals (Figure 4A).…”
Section: Both the Candidate Nano11-based Vaccines Elicited Strong Vir...mentioning
confidence: 99%